2001
DOI: 10.1254/jjp.86.47
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Effects of Benzodiazepines on the Exploratory Behaviors of Mice on a Hole-Board by Diabetes

Abstract: ABSTRACT-The effect of diabetes on the emotional behavior of mice was examined using an automatic hole-board apparatus. Changes in the emotional state of mice were evaluated in terms of changes in exploratory activity; i.e., total locomotor activity, numbers and duration of rearing and head-dipping, and latency to the first head-dipping. The number and duration of head-dipping in diabetic mice were less than those in non-diabetic mice. Diazepam (0.1 -0.56 mg/ kg, i.p.) dose-dependently increased the number and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…)-treated mice is likely to be reflected in the hypolocomotor activity. We previously reported that diazepam at 0.3 mg / kg exerted the significant anxiolytic-like effect in the mouse hole-board test (20). Therefore, the freezing behavior in the elevated openplatform test may not be affected by diazepam at the dose having no effect on locomotor activity.…”
Section: Resultsmentioning
confidence: 95%
“…)-treated mice is likely to be reflected in the hypolocomotor activity. We previously reported that diazepam at 0.3 mg / kg exerted the significant anxiolytic-like effect in the mouse hole-board test (20). Therefore, the freezing behavior in the elevated openplatform test may not be affected by diazepam at the dose having no effect on locomotor activity.…”
Section: Resultsmentioning
confidence: 95%
“…Guyot et al (27) indicated that chronic hyperglycemia reduces extracellular GABA levels. Furthermore, we previously reported that the anxiolytic effect of diazepam in an unfamiliar environment was decreased by diabetes in mice (28). Therefore, it is possible that the decreased efficacy of pentobarbital in diabetic mice may be due, at least in part, to the changes in GABAergic systems.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we subjected 4-week-old mice to OBX and the behavioral test was performed 2 weeks after surgery, since in general the hole-board test is used in 6-week-old mice (17,19,20). Mice were anesthetized with sodium pentobarbital (50 mg / kg, i.p.)…”
Section: Obxmentioning
confidence: 99%